1989
DOI: 10.1111/j.1365-2958.1989.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and phase variation of gonococcal P.11 genes in Escherichia coli involves ribosomal frameshifting and slipped‐strand mispairing

Abstract: Expression and phase variation of Neisseria gonorrhoeae P.II genes in Escherichia coli were studied using TnphoA fusions. Fusions were created in the P.IIc gene of N. gonorrhoeae JS3 using lambda TnphoA-1 and were characterized by restriction digestion and dideoxy sequencing. Three fusions were chosen for further study; Tnp7 (fusion junction at mature amino acid 7), Tnp57 (amino acid 57), Tnp66 (amino acid 66). All fusions were in frame with the P.IIc coding sequence but were out of frame with the purported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Analyses of flanking DNA sequences demonstrated that at least two of these strains are only distantly related to each other (see below), indicating that the mutations probably arose independently. A number of other prokaryotes, including Neisseria and Mycoplasma, regulate expression of certain proteins by inactivating their genes through slipped-strand mispairing during replication of repetitive DNA sequences (Belland et al, 1989;Murphy et al, 1989;Yogev et al, 1991). It has been hypothesized that slipped-strand mispairing modulates expression of the antigenic B. burgdorferi VraA lipoprotein , and our results suggest that a similar regulatory process may also be at work in the bapA gene.…”
Section: B Burgdorferi Bapa Genesmentioning
confidence: 55%
“…Analyses of flanking DNA sequences demonstrated that at least two of these strains are only distantly related to each other (see below), indicating that the mutations probably arose independently. A number of other prokaryotes, including Neisseria and Mycoplasma, regulate expression of certain proteins by inactivating their genes through slipped-strand mispairing during replication of repetitive DNA sequences (Belland et al, 1989;Murphy et al, 1989;Yogev et al, 1991). It has been hypothesized that slipped-strand mispairing modulates expression of the antigenic B. burgdorferi VraA lipoprotein , and our results suggest that a similar regulatory process may also be at work in the bapA gene.…”
Section: B Burgdorferi Bapa Genesmentioning
confidence: 55%
“…However, unlike Opc, Opa protein expression is regulated at the translational level (Stern et al, 1986;Kawula et al, 1988;Belland et al, 1989). Opa proteins are encoded by a family of opa genes scattered throughout the bacterial genome Bihlmaier et al, 1991), and vary dramatically in sequence, particularly at two cell-surface-exposed hypervariable regions (Connell et al, 1988;Aho et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…gonorrhoeae (James & Swanson, 1978;Swanson et a/., 1988;Jerse et al, 1994). Phase variation (reversible on-off switching) of Opa proteins results from alterations in reading frame caused by changes in the number of pentanucleotide repeats (CTCTT) in the signal-peptideencoding region of opa genes (Stern et al, 1986;Stern & Meyer, 1987;Kawula et al, 1988;Belland et al, 1989Belland et al, , 1997Murphy et al, 1989). Antigenic variation among the Opa proteins of an individual strain is a consequence of alternate expression from multiple opa loci in the bacterial chromosome, encoding proteins with different antigenic characteristics.…”
Section: Introductionmentioning
confidence: 99%